COVID-19 infodemic and Indonesian emotional and mental health state - Rizma Adlia Syakurah; Violantina Linardi; Ilsyafitri Bonita (Intelektual Pustaka Media Utama, 2021)
The currently ongoing coronavirus disease 2019 (COVID-19) pandemic induced built-up fear and anxiety notably with non-stop surge information through all media. Understanding of emotional and mental health impact during this state is urgently needed for further intervention. This study aimed to identify the current pattern of depression, anxiety, stress and, emotional disorder presented in the society and the association between Indonesian news-seeking behaviour and their mental health state during the COVID-19 outbreak. A cross-sectional study with 1,508 respondents was carried out with online questionnaire consisted of depression, anxiety, and stress scale (DASS) and SRQ-20 as assessment tools that was distributed through social media platforms from April 2−June 8, 2020. Data was analyzed using Mann Whitney, Kruskal Wallis, Post Hoc with Bonferroni, and Chi-square test (p<0.05). As much as 20.7% of respondents were depressed, 36.9% had anxiety, 25.5% had been stress, and 27.6% had emotional disorder. Most respondents actively searched about COVID-19 especially through television and social media platforms such as Twitter, Facebook, and Instagram. Type of news and level of trust in COVID-19 news were the factors that influenced emotional and mental health state (p=<0.05). Providing mental health support in a timely and appropriate manner through a hotline team, media, or multidisciplinary team, including mental health professional is an important thing that the Indonesian government must do to help the Indonesian people through this pandemic.